Percepciones Y Caracterización De Pastizales En Los Cantones Joya De Los Sachas Y Francisco Orellana - Raúl Lorenzo González Marcillo; Juan Rafael Perez Pupo (European Scientific Journal, ESJ, 2018)
The study allowed to determine the perceptions and characterization of the pastures in farms of livestock producers and researchers in the Canton Sachas and Francisco Orellana, Province of Orellana, Ecuador, whose objective was to know the use and management of Amazonian tropical pastures. Seventeen cattle farms of 8 communities were characterized to observe the characterization of the farmers, land use, use of forage banks, pasture management and bovine cattle housing. A semi-structured interview was designed to collect primary information about the problem under investigation. When characterizing the farmers, in relation to land use, previously 47.5% of the producers were engaged in agriculture, today 85.9% carry out livestock work with silvopastoral practices and only 14.1% are dedicated to agriculture. production of coffee and cocoa. Regarding the use of feed banks, 35.29% have more food for their animals and 5.88% have better environmental conditions. In addition, 77.6% of the farmers mentioned that they have improved their production with the use of the feed bank. In summary, the results indicate that small and medium producers can benefit from silvopastoral systems as an alternative to improve production and not affect the environment.